The joy of sharing seeds: organizing a successful seed fair - Vernooy, Ronnie (Bioversity International, 2019)
A seed fair is an activity to create awareness about and appreciate local crop diversity, exchange seed and related knowledge, and celebrate farmers’ efforts to conserve agrobiodiversity. It takes considerable time and effort to organize a seed fair. This brief graphically presents the steps involved in organzing a seed fair at the Agyauli Community Seedbank, Nawalparasi, bringing together 30 members of 10 community seedbanks from the terai (the southern lowland) region of Nepal.